2021
DOI: 10.3390/s21155119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Factors on Cyber Security within Healthcare Organisations: A Systematic Review

Abstract: Background: Cybersecurity is increasingly becoming a prominent concern among healthcare providers in adopting digital technologies for improving the quality of care delivered to patients. The recent reports on cyber attacks, such as ransomware and WannaCry, have brought to life the destructive nature of such attacks upon healthcare. In complement to cyberattacks, which have been targeted against the vulnerabilities of information technology (IT) infrastructures, a new form of cyber attack aims to exploit human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 73 publications
(230 reference statements)
2
41
0
2
Order By: Relevance
“…The SECANT plafofrm will be validated through four different Pilot Use Cases that are aiming (i) to validate SECANT's ability to improve transportation safety and ensure zero-error delivery of patients transported using timeconstraint Emergency Medical Services (Protecting the connected ambulance of the future), (ii) to validate SECANT's efficiency to deal with cascading effects of cyber threats and with propagated vulnerabilities in connected healthcare infrastructures, as well as in remote healthcare settings (Cyber security for connected medical devices and mobile applications [23], [24]), (iii) To validate the capabilities of SECANT to ensure privacy, data protection and accountability when operational data is being exchanged within the healthcare supply chain (Health data protection in the healthcare supply chain) and (iv) to validate the capabilities of SECANT's cyber security training modules and critical infrastructure cyber range (Cyber Security training). These Pilot Use Cases will be further discussed on separate papers that are under preparation.…”
Section: Use Casesmentioning
confidence: 99%
“…The SECANT plafofrm will be validated through four different Pilot Use Cases that are aiming (i) to validate SECANT's ability to improve transportation safety and ensure zero-error delivery of patients transported using timeconstraint Emergency Medical Services (Protecting the connected ambulance of the future), (ii) to validate SECANT's efficiency to deal with cascading effects of cyber threats and with propagated vulnerabilities in connected healthcare infrastructures, as well as in remote healthcare settings (Cyber security for connected medical devices and mobile applications [23], [24]), (iii) To validate the capabilities of SECANT to ensure privacy, data protection and accountability when operational data is being exchanged within the healthcare supply chain (Health data protection in the healthcare supply chain) and (iv) to validate the capabilities of SECANT's cyber security training modules and critical infrastructure cyber range (Cyber Security training). These Pilot Use Cases will be further discussed on separate papers that are under preparation.…”
Section: Use Casesmentioning
confidence: 99%
“…Additionally, due to very open nature of community and social healthcare settings it is very difficult to implement data access and usage related controls. Nifakos et al (2021) in their research analyzed the impact of human factors on cybersecurity in healthcare organizations and suggested that successful adoption of digital transformation strategies in the healthcare industry depends upon the successful acceptance among healthcare professionals toward addressing risks posed by cyber threats. Therefore, it is important to provide cyber-security awareness and training to healthcare professionals (Nifakos et al, 2021).…”
Section: Challenges In Information Security and Privacymentioning
confidence: 99%
“…While there are a range of technical vulnerabilities that can be exploited through cyberattack, the greatest vulnerability is the human element—that is, the manipulation of the clinician, such as the nurse, to gain access to the digital infrastructure. This type of attack—known as social engineering —is increasingly sophisticated and often involves targeting specific nurses through their social media profiles (Nifakos et al, 2021). These attacks are successful because nurses are often overworked in resource constrained environments (Nifakos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This type of attack—known as social engineering —is increasingly sophisticated and often involves targeting specific nurses through their social media profiles (Nifakos et al, 2021). These attacks are successful because nurses are often overworked in resource constrained environments (Nifakos et al, 2021). Therefore, a key concern of nurse managers should be to consider workload in terms of the degree increases cyberattack vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%